2014
DOI: 10.1007/s11064-014-1434-8
|View full text |Cite
|
Sign up to set email alerts
|

Stress in Neonatal Rats with Different Maternal Care Backgrounds: Monoaminergic and Hormonal Responses

Abstract: The first 2 weeks of life in rats are known as the stress hyporesponsive period because stress responses in pups are diminished as compared to adult animals. However, it is considered a critical period in development in which infant rats are susceptible to environmental events, such as stressful stimuli and quality of maternal care received. These early life events have long-lasting effects, shaping a variety of outcomes, such as stress responsivity. This study investigated the effects of maternal care and sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 64 publications
1
9
0
Order By: Relevance
“…Altered OT levels have been documented in rodents exposed to low levels of naturally occurring maternal care or experimentally induced early separation . These effects have been observed in specific OT‐innervated brain regions, such as the HYP or AMY, as well as in the plasma .…”
Section: Oxytocin Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Altered OT levels have been documented in rodents exposed to low levels of naturally occurring maternal care or experimentally induced early separation . These effects have been observed in specific OT‐innervated brain regions, such as the HYP or AMY, as well as in the plasma .…”
Section: Oxytocin Systemmentioning
confidence: 99%
“…Altered OT levels have been documented in rodents exposed to low levels of naturally occurring maternal care or experimentally induced early separation . These effects have been observed in specific OT‐innervated brain regions, such as the HYP or AMY, as well as in the plasma . Observed changes are generally in the direction of blunted OT levels in those exposed to early adversity, although it has been proposed that prolonged exposure may lead to a rise in OT levels as a way of protecting the system from the deleterious effects of stress .…”
Section: Oxytocin Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, quality of maternal behavior has been linked to differences in oxytocin concentrations and OXTR expression observed in animal models ( 9 , 36 ). For example, high levels of maternal licking resulted in increased plasma oxytocin concentrations in neonatal rats ( 37 ). Furthermore, Kojima and colleagues ( 38 ) found that maternal skin-to-skin contact stimulates rat pups’ central oxytocin concentrations.…”
Section: Oxytocin and The Early Social Environmentmentioning
confidence: 99%
“…OXT, AVP, and PRL are primary mediators of maternal care and have been implicated in the etiology and symptomology of stress related affective disorders (Faron-Górecka et al, 2014; Insel and Young, 2001; Mann and Bridges, 2001; Nephew, 2012; Rilling and Young, 2014; Zamorano et al, 2014). Furthermore, OXT is a key mediator of the reciprocal nature of the mother-infant bond (Carter, 2003; Feldman et al, 2011; Feldman et al, 2007; Henriques et al, 2014; MacKinnon et al, 2014; Mogi et al, 2011). The current study investigated additional neural targets that may be involved in the adverse effects of ECSS on the F1 generation and represent novel preventative and/or treatment targets.…”
Section: Introductionmentioning
confidence: 99%